Study on the spectral selectivity of graphene/superconductor photonic crystals at low temperature. (June 2019) - Xie, Xun; Liu, Yu-Jie; Ju, Lu; Hao, Jiong-Ju; Yang, Hong-Wei
Highlights: A novel spectral selectivity material is proposed based on photonic crystal structure; each unit cell is composed of graphene layer and superconductor layer. The optical properties of this structure in the visible to near infrared range are numerically simulated by means of finite-difference time-domain method. Furthermore, we have discussed the effect of structural parameters and external temperature on the spectral selectivity inside the structure. The results show that the spectral selectivity is very sensitive to the thickness of superconductor layer, period number and temperature variation, and the spectral range of visible transmission and near infrared reflectance can be tuned by changing these parameters. Abstract: In this work, a novel spectral selectivity material is proposed based on photonic crystals structure, each unit cell is composed of graphene layer and superconductor layer. The optical properties of this structure in the visible to near infrared range are numerically simulated by means of finite-difference time-domain method. Furthermore, we have discussed the effect of structural parameters and external temperature on the spectral selectivity inside the structure. The result shows that the spectral selectivity is very sensitive to the thickness of superconductor layer, period number and temperature variation, and the spectral range of visible transmission and near infrared reflectance can be tuned by changing these parameters. In addition, we find the (Graphene/YBCO) 10 structure can be transparent in visible light while high-performance shielding in near infrared at the period number is 10, the external temperature is 55 K and the thickness of graphene layer and superconductor layer are 0.34 nm and 50 nm, respectively. In fact, this novel material may be useful in designing of visible-near infrared filter at low temperature.